Utilization of Smart Whiteboard Media Based on Educational Games to Train Students' Creative Thinking Skills - Wardani, Agnia Rizqi; Ibrahim, Muslimin; Widodo, Wahono (PrimaryEdu : Journal of Primary Education, 2022)
This study aims to develop educational games that use smart whiteboard media, and related devices such as Learning Implementation Plans (RPP), Student Worksheets, and Creative Thinking Test Sheets that are appropriate to be used to practice creative thinking skills of fourth-grade elementary school students. This study uses a 4D development model (define, design, develop, and disseminate), which is limited to the third stage (develop). The use of game-based smart whiteboard media and related devices was then validated by experts and the results obtained that the media was valid and could be used in research. The study was conducted on 24 fourth-grade students of MI Miftahul Ulum with One Group Pretest-Posttest Design. The data collection instrument used was a media validation sheet filled out by three experts, a lesson plan implementation observation sheet, a student activity observation sheet, a creative thinking skills test sheet, and a student response questionnaire sheet. Methods of data analysis were carried out in the form of the media validation analysis, analysis of the implementation of learning activities, analysis of student activities, analysis of creative thinking skills, and analysis of student responses. The results of the research and research discussions can be concluded that the use of smart whiteboard media based on educational games to train students' creative thinking skills that have been developed is valid, practical, and effective.Keywords:Â smart whiteboard, educational games, creative thinking skills